Analisis Semiotika Riffaterre pada Puisi al-Hubbu wa al-Hurriyya Karya Ali Ahmad Bakathir - Lailatul Istiqlaliyah; Mirwan Akhmad Taufiq; Atiq Mohammad Romdlon (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2025)
The poem al-Hubbu wa al-Hurriyah is the work of Ali Ahmad Bakathir, an Arab poet born in Indonesia. Not many Indonesian people understand this poem in depth. This study aims to reveal the semiotics of the poem al-Hubbu wa al-Hurriyah from the perspective of heuristic, hermeneutic, model, matrix, and hypnogram readings. The method used is descriptive qualitative with the techniques of collecting, selecting, and interpreting. The results of this study show heuristic, hermeneutic, model, matrix, and hypogram readings. Through heuristic reading, the linguistic meaning is shown in the form of a translation of the poem al-Hubbu wa al-Hurriyah in general, and hermeneutic reading provides a deep understanding of the meaning of the poem, where love is a force that drives the struggle to achieve independence. In this poem, the matrix and model are related to the themes of love and independence. In addition, the program that appears is related to the verses of the Qur'an, which contain the spirit, patience and persistence of a struggle and love for the homeland.